The Relationship between the naming of UIN Palembang with Raden Fatah the Sultanate of Demak: a historical perspective - Otoman, Otoman; Antasari, Rr Rina; Sari, Renny Kurnia; Fakhriya, Siti Dini; Ibrahimian, Hojjatullah (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2023)
This article discusses the relationship between the naming of UIN Palembang and the name Raden Fatah from a historical perspective. This study aims to reveal the historical facts behind the naming relationship of UIN Palembang which uses the name Raden Fatah which is synonymous with the Sultanate of Demak. The method used is descriptive qualitative which refers to historical research analysis techniques. The historical research process goes through four stages, namely heuristics, source criticism, interpretation, and historiography. The research results reveal two historical facts behind the naming. First, the influence of Raden Fatah's Islamization in Palembang has not only crystallized in the collective memory of the community, but is also neatly preserved in historical traces that can still be seen today. This historical fact confirms the influence of Raden Fatah's Islamization on Palembang, South Sumatra. Second, the naming of UIN Palembang with the name Raden Fatah is historically tied to the relationship between the figures of Raden Fatah and Palembang. The knot of Raden Fatah's character can be identified through four relations: namely location (place) relations, mission relations, contribution relations, and historical trace relations. These four relationships are the argumentative historical facts behind naming UIN Palembang with the name UIN Raden Fatah.